Realgar nanoparticles versus ATO arsenic compounds induce in vitro and in vivo activity against multiple myeloma. (19th October 2017) - Cholujova, Danka; Bujnakova, Zdenka; Dutkova, Erika; Hideshima, Teru; Groen, Richard W.; Mitsiades, Constantine S.; Richardson, Paul G.; Dorfman, David M.; Balaz, Peter; Anderson, Kenneth C.; Jakubikova, Jana
Summary: Multiple myeloma (MM), a B cell malignancy characterized by clonal proliferation of plasma cells in the bone marrow, remains incurable despite the use of novel and conventional therapies. In this study, we demonstrated MM cell cytotoxicity triggered by realgar (REA; As4 S4 ) nanoparticles (NREA) versus Arsenic trioxide (ATO) against MM cell lines and patient cells. Both NREA and ATO showed in vivo anti‐MM activity, resulting in significantly decreased tumour burden. The anti‐MM activity of NREA and ATO is associated with apoptosis, evidenced by DNA fragmentation, depletion of mitochondrial membrane potential, cleavage of caspases and anti‐apoptotic proteins. NREA induced G2 /M cell cycle arrest and modulation of cyclin B1, p53 (TP53), p21 (CDKN1A), Puma (BBC3) and Wee‐1 (WEE1). Moreover, NREA induced modulation of key regulatory molecules in MM pathogenesis including JNK activation, c‐Myc (MYC), BRD4, and histones. Importantly, NREA, but not ATO, significantly depleted the proportion and clonogenicity of the MM stem‐like side population, even in the context of the bone marrow stromal cells. Finally, our study showed that both NREA and ATO triggered synergistic anti‐MM activity when combined with lenalidomide or melphalan. Taken together, the anti‐MM activity of NREA was more potent compared to ATO, providing the preclinical framework for clinical trials to improve patient outcome in MM.